Enhancing Students’ Vocabulary Skill Through Team Game Tournament Strategy in University - Susana, Intan; Ngaisah, Siti (Jurnal Pembelajaran dan Ilmu Pendidikan, 2025)
This study focuses on enhancing vocabulary skills in STITMA Blitar for students through the Team Game Tournament (TGT) strategy. It is a classroom management technique in which students are placed in mixed ability teams to compete in a game based style of learning. The purpose of it is to create an effective classroom environment. The mayor of problem is the insufficient vocabulary proficiency that impacts students' communication abilities. The research involved organizing students into groups and introducing a series of educational games designed to improve their vocabulary. The researcher concluded that the vocabulary test of pair of the students increased from 63.00 in the Cycle 1 to 76.50 in Cycle 2. It shown by the improvement of students’ vocabulary test in group, shown that the students’ mean score was 72.00 in the Cycle 1 and increased to be 81.00 in the Cycle 2. The results revealed a significant boost in vocabulary skills, with many students indicating that the learning experience was enjoyable and effective. This approach successfully encouraged motivation and collaboration,and creating more interactive and engaging educational atmosphere.